2014
DOI: 10.17659/01.2014.0052
|View full text |Cite
|
Sign up to set email alerts
|

Double Right Coronary Artery Arising From Separate Ostia

Abstract: We present a rare case of double right coronary artery (RCA) arising from separate ostia. A 62 years old male patient was admitted with acute onset retrosternal chest pain. ECG was suggestive of sinus rhythm with intraventicular conduction delay and pathological q waves in D3 and avF derivations without any significant ST segment elevations. In the coronary angiography, we detected double RCA, each had its own ostium arising separately from right aortic sinus with complete occlusion seen in one RCA. Plaques we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
0
1
Order By: Relevance
“…The double right coronary artery usually diagnosed by conventional coronary angiography or multi-detector computed tomography. In our study the incidence of double right coronary artery was 3.3% and that disagreed with Ermis et al .,2014 ; Kunimasa et al, 2007;Erbagci et al, 2006 who found 0.01% , 0.07% and 0.01% respectively [17,11,18] but our result nearly corresponded to Angelini et al,1999 who recognized 1.23%. [19] Also the incidence increased in patients who lived in rural area and there is no similar study related to this issue but this differences in the incidence may related to geographical and genetic bases [20] or due to physicians in the other countries define this topic as high take off large ventricular artery from right coronary artery .…”
Section: Discussioncontrasting
confidence: 87%
“…The double right coronary artery usually diagnosed by conventional coronary angiography or multi-detector computed tomography. In our study the incidence of double right coronary artery was 3.3% and that disagreed with Ermis et al .,2014 ; Kunimasa et al, 2007;Erbagci et al, 2006 who found 0.01% , 0.07% and 0.01% respectively [17,11,18] but our result nearly corresponded to Angelini et al,1999 who recognized 1.23%. [19] Also the incidence increased in patients who lived in rural area and there is no similar study related to this issue but this differences in the incidence may related to geographical and genetic bases [20] or due to physicians in the other countries define this topic as high take off large ventricular artery from right coronary artery .…”
Section: Discussioncontrasting
confidence: 87%